2022
DOI: 10.1021/acs.accounts.2c00470
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Alkyl Carbonyl Complexes: From Iconic Stoichiometric Textbook Reactions to Catalytic Applications

Abstract: Conspectus The activation of weakly polarized bonds represents a challenging, yet highly valuable process. In this context, precious metal catalysts have been used as reliable compounds for the activation of rather inert bonds for the last several decades. Nevertheless, base-metal complexes including cobalt, iron, or nickel are currently promising candidates for the substitution of noble metals in order to develop more sustainable processes. In the past few years, manganese(I)-based complexes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…1 Whereas cobalt, iron and nickel catalysts are well-established for C–H functionalization, in particular for C–H borylation, 2 manganese has received less attention, despite its sustainable supply and environmentally benign nature. The chemistry of Mn( i ) tricarbonyl complexes is a mature field, with the [Mn(Cp′)(CO) 3 ] (MMT, Cp′ = MeC 5 H 4 ) 3 complex used as a gasoline additive, and complexes derived from fac -{Mn(LL)(CO) 3 } fragments known as catalysts for CO 2 reduction, 4 hydrogenation, 5 hydrofunctionalization 6 and other small-molecule functionalization processes. 7 In contrast, the chemistry and catalytic applications of Mn( i ) and Mn( ii ) complexes lacking strong-field CO ligands remain underexplored, likely as a result of the challenges associated with controlling their high-spin states.…”
Section: Introductionmentioning
confidence: 99%
“…1 Whereas cobalt, iron and nickel catalysts are well-established for C–H functionalization, in particular for C–H borylation, 2 manganese has received less attention, despite its sustainable supply and environmentally benign nature. The chemistry of Mn( i ) tricarbonyl complexes is a mature field, with the [Mn(Cp′)(CO) 3 ] (MMT, Cp′ = MeC 5 H 4 ) 3 complex used as a gasoline additive, and complexes derived from fac -{Mn(LL)(CO) 3 } fragments known as catalysts for CO 2 reduction, 4 hydrogenation, 5 hydrofunctionalization 6 and other small-molecule functionalization processes. 7 In contrast, the chemistry and catalytic applications of Mn( i ) and Mn( ii ) complexes lacking strong-field CO ligands remain underexplored, likely as a result of the challenges associated with controlling their high-spin states.…”
Section: Introductionmentioning
confidence: 99%
“…1 While it has long been considered to be catalytically only poorly active, recent work demonstrated that manganese-based homogeneous catalysis is viable. [1][2][3] Major contributions stem from Mn(I) pincer complexes, which have been used in synthetically relevant reactions, such as reduction, dehydrogenation and dehydrogenative coupling reactions. [4][5][6][7] In contrast, higher-valent Mn(II) and Mn(III) compounds have been less widely employed, with most applications related to redox catalysis, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In particular, manganese carbonyls are widely used as reagents in organometallic chemistry for polymerization, 25 carbonylation, reduction, and activation of different robust bonds. 26 Iron is the 4th most abundant element in the Earth's crust, and also the most abundant element in Earth as a whole, ahead of oxygen and silicon. 27 This metal has been crucial for development of tools and weapons since prehistorical times, and to this day plays major role in modern industries and technology.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In particular, manganese carbonyls are widely used as reagents in organometallic chemistry for polymerization, 25 carbonylation, reduction, and activation of different robust bonds. 26…”
Section: Introductionmentioning
confidence: 99%